MOTIVASI KERJA PEGAWAI DI KANTOR UPT. MUSEUM DAN TAMAN BUDAYA DINAS PENDIDIKAN DAN KEBUDAYAAN PROVINSI SULAWESI TENGAH - Syafril, Mohammad (Katalogis, 2021)
This research was done in purpose of understanding Employee Work Motivation at UPT. Museum andÂ Cultural Park Education and Culture Agency Of Central Sulawesi Province. In this research, write used descriptive qualitative method, by using need hierarchy theory (A. Masllow) which consist of (1) physiological need, (2) Security need, (3), Sosial need, (4) Appreciation need, (5), Self Actualization need, subject in this research are employee of UPT Museum and Cultural Park education and culture agen which consist of five (5) people as measureddata collected by in-depth interview. Meanwhile, the resouce data was separated as primer and seconder data, while data collected through interview, observation, and documentation. Andthen, data analysis was done in steps such as data reduction, data data presentation, and conclusion. From this research, writer concluded occurring phenomena suchsuch as 1) there are dissatisfaction regarding salary that considered as insufficient to acquiring basic need such as food, clothing, and household items, especially interim employee with yheir stipends. 2) employee still feels unsafe in their working environment which is caused by two (2) factor such as very old office building and the absent of security team or SATPOL-PP in UPT. Museum andÂ Cultural Park Education and Culture Agency Of Central Sulawesi Province. 3), there was disharmony between employee and employee wgich disrupted social relationship which empact working process resulting in underperforming. 4) disharmony between employee and employee causing the lack of appreciation or promotion for reserve employee resulting in apathy and lack of enthusiasm. 5). There are employee who regards themselves as capable in their chosen fied but unutilized and their need for self_actualization was not satisfied. These five need was not actualized which is resulting in low employee motivation in working prosces.